Ladakhi Kitchen - Reifenberg, Gabriele (Petits Propos Culinaires, 2004)
The book of this name was reviewed by James Crowden in the last issue of PPC. I was so intrigued by it that I obtained from its author permission to reprint her introduction and fifteen of her favourite recipes, together with a couple of the illustrations by the artist the late Abdul Salam Tak, and the poem by Sonam Sopari. Prospect Books customers will not be surprised at the close relationship of the Ladakhi kitchen to that of Tibet described by Rinjing Dorje in his Food in Tibetan Life. Rinjing, by the way, still flourishes in Seattle, as does his family. He has been able to revisit his homeland. I have made a few small alterations to the text to accommodate it to its new setting, and I should point out that the book has its full quiver of practical tips, pronunciation guide and glossary. It also has a nice map which I have not reproduced here. I am very grateful to Gabriele Reifenberg, who was assisted by Phuntsog Angmo and Tsewang Dolma, for allowing this reproduction. Should you want copies of the book itself, it can be bought for a minimum donation of £8.00 (to include postage and packing) from the author at 5 Owlstone Road, Cambridge CB3 9JH.